THE ROLES OF TEACHERS AND SCHOOLS IN CONDUCTING EFFECTIVE CLASSROOM ASSESSMENT - I Nyoman Suwandi (Bajang Institute, 2023)
Assessment is one of the activities carried out to measure and assess the level of achievement of the curriculum and the success or failure of the learning process. The principles and strategies of the classroom assessment are used to guide how teachers always carry out intensive assessments of their students to find out their students' progress. This research examined the role of teachers and schools in implementing classroom assessments. This research method is a qualitative method where the data were analysed descriptively. Data required for this study were collected through interviews and field observations. This study found that teachers and schools have an essential role in implementing the assessment. The active role of teachers and schools in carrying out class assessments improve the quality of learning so that students' abilities can always increase. This research has implications that teachers and schools must increase their role in implementing class assessments so that schools can produce higher-quality graduates